Analisis Kinerja Keuangan Pemerintah Provinsi Sulawesi Utara Tahun Anggaran 2009-2014 - Rondonuwu, Giftovel (JURNAL RISET BISNIS DAN MANAJEMEN, 1996)
Effectiveness Ratio PAD showed effective criteria to the regional finance performance because it can be seen that in the six years of research, namely in the first 5 years from 2009 to 2013 in the category Effectively that means the government of North Sulawesi province is able to realize the planned PAD compared with targets set by the real potential of the region, Further decentralization indicates that the Government of North Sulawesi province is still not fully meet the total revenue with this own-source revenue. Suitability ratio indicates greater volumes of realization of operating expenditures rather than capital expenditure. Growth ratio shows the number of unstable from 2009 to 2014. Keyword: Regional Finance Performance, Budgets